Fatty acid metabolism related gene MECR contributes to the progression of prostate cancer - Yifan Liu; Lilin Wan; Yuxuan Chen; Ruixin Zhang; Yi Xia; Ming Chen; Xiang Huang; Ruiji Liu (Cancer Cell International)
Abstract Background Prostate cancer (PCa) is the most common urological malignancy and second only to lung cancer in incidence among men. Its prognosis varies widely due to its heterogeneity. Research indicates that fatty acid metabolism may play a role in tumor development. Methods The gene expression profiles of PCa cell lines (GSE6919) in GEO database were analyzed to identify differentially expressed genes and their significance in relation to progression-free interval. The R package was employed to assess overall survival significance and clinicopathological features. The study investigated the effects of gene mutations and methylation on PCa and their correlation with immune cell infiltration in the tumor microenvironment, utilizing cBioPortal and UALCAN resources. TIMER was used in the TCGA project to compare the expression of MECR in tumours and in adjacent normal tissue for different tumours or for specific tumour subtypes. Furthermore, we examined the impact of hub genes on PCa progression through RT qPCR, immunohistochemistry, and cellular assays. Results The MECR gene, which plays a role in fatty acid metabolism, has been implicated in the development and progression of PCa. Its expression levels are significantly associated with clinical features, survival outcomes, and prognosis in PCa. Comprehensive analyses of MECR mutations and methylation levels further underscore its involvement in the progression of prostate cancer. Additionally, MECR is closely associated with the immune microenvironment and immune cell infiltration in PCa. Furthermore, the in vitro and in vivo data indicated that MECR plays a role in PCa proliferation, migration, and invasion. Conclusion MECR has significant potential for research and application in the assessment of PCa prognosis and the regulation of the immune microenvironment.